The Genotype (A to H) Dependent N-terminal Sequence of HBV Large Surface Protein Affects Viral Replication, Secretion and Infectivity - Ou, Guomin; He, Lingyuan; Wang, Luwei; Song, Ji; Lai, Xinyuan; Tian, Xing; Wang, Lei; Zhang, Kai; Zhang, Xuechao; Deng, Juan; Zhuang, Hui; Xiang, Kuanhui; et al. (Frontiers in Microbiology, 2021)
Genetic variability has significant impacts on biological characteristics and pathogenicity of hepatitis B virus (HBV), in which the N-terminal sequence of the presurface 1 (preS1) region of HBV large surface protein (LHBs) displays genotype (GT) dependent genetic heterogeneity. However, the influence of this heterogeneity on its biological roles is largely unknown. By analyzing 6560 full-length genome sequences of GTA-GTH downloaded from HBVdb database, the preS1 N-terminal sequences were divided into four representative types, namely C-type (representative of GTA, GTB, and GTC), H-type (GTF and GTH), E-type (GTE and GTG), and D-type (GTD), respectively. We artificially substituted the preS1 N-termini of GTC and GTD plasmids or viral strains with each sequence of the four representative types. The roles of preS1 N-terminus on HBV replication, secretion and infectivity were investigated using HepG2 or HepG2-NTCP cells. In the transfection experiments, the results showed that the extracellular HBsAg levels and HBsAg secretion coefficients in D- and E-type strains were significantly higher than those in C- and H-type strains. D-type strain produced more extracellular HBV DNA than C-type strain. We further observed that D-, H-, and E-type strains increased the levels of intracellular replicative HBV DNAs, comparing with C-type strain. In the infection experiments, the levels of extracellular HBeAg, intracellular HBV total RNA and pgRNA/preC mRNA in D- and E-type strains were markedly higher than C and H-type ones. Our data suggest that the preS1 N-termini affect HBV replication, secretion and infectivity in a genotype dependent manner. The C- and H-type strains prefer to attenuate HBsAg secretion, while the strains of D- and E-type promoted infectivity. The existence and function of the intergenotypic shift of preS1 in naturally occurring recombination requires further investigation, as the data we acquired are mostly related to recombinant preS1 region between N-terminus of preS1 from genotypes A-H and the remaining preS1 portion of GTC or GTD.